Kinetic study of Oxidation of 2-Phenylethanol by N-Chlorosuccinimide (International Journal of Scientific Research in Science and Technology, 2025)
The Kinetics of oxidation of 2-Phenylethanol by N-Chlorosuccinimide has been Studied spectrophotometrically in presence of Sulphuric acid in aqueous acetic acid medium in the temperature range 293-313K The reaction is first order with respect to both [2-Phenylethanol] and N-chlorosuccinimide [NCS]. The Thermodynamic parameters for the slow step were computed and calculated. Effect of ionic strength and dielectric constant of medium has also been studied. A suitable mechanism has been proposed.
Keywords: 2-Phenylethanol; N-chlorosuccinimide; oxidation; kinetics; mechanism